Digitization, replication, and modification of physical surfaces using two-photon lithography. (June 2020) - Maddox, Shelby; Afshar-Mohajer, Mahyar; Zou, Min
Abstract: Many surfaces in nature have interesting topographies that lead to properties that may be desirable for engineering applications, such as superhydrophobicity (lotus leaf), high adhesion (frog toes), and drag reduction (shark skin). Although simple replication processes via polydimethylsiloxane molding have been used to replicate these topographies, they cannot be used to modify or combine these topographies for added functionality. This paper presents a novel method to digitize an arbitrary surface, either from nature or manmade, replicate it, modify it, and print it. A banana skin, an eastern wahoo leaf, and a coin were digitized using a 3D laser scanning confocal microscope and modified with arbitrary additional textures. The digitized surfaces were then printed using a UV-sensitive polymer based on two-photon polymerization. The printed surfaces replicate the original surfaces with submicron accuracy; and additional textures were added to illustrate the ability to modify the surface topography. This method enables novel surface topographies to be created that cannot be found in nature.